Interface engineering of an AlNO/AlGaN/GaN MIS diode induced by PEALD alternate insertion of AlN in Al2O3. Issue 19 (16th February 2017) - Wang, Qian; Cheng, Xinhong; Zheng, Li; Shen, Lingyan; Li, Jingjie; Zhang, Dongliang; Qian, Ru; Yu, Yuehui
Abstract : In this paper, AlNO nano-films have been deposited on an AlGaN/GaN heterojunction by alternating growth of AlN and Al2 O3 using plasma enhanced atomic layer deposition (PEALD). Abstract : In this paper, AlNO nano-films have been deposited on an AlGaN/GaN heterojunction by alternating growth of AlN and Al2 O3 using plasma enhanced atomic layer deposition (PEALD). With optimized AlN layer insertion in Al2 O3, the oxygen is effectively blocked from diffusing to the AlGaN surface and the formation of detrimental Ga–O bonds is significantly suppressed. Owing to the negative fixed charges in Al2 O3, provided by the incorporated nitrogen, the flat band voltage ( V fb ) of the AlNO/AlGaN/GaN metal–insulator–semiconductor (MIS) diode exhibits a positive shift of 1.50 V, compared with the Al2 O3 /AlGaN/GaN MIS diode. Markedly reduced hysteresis and frequency-dispersion in the C – V characteristics have also been observed at the AlNO/AlGaN interface. Furthermore, the interface states density ( N it ) at the AlNO/AlGaN interface has been reduced by one order of magnitude compared with the N it at the Al2 O3 /AlGaN interface, and the border traps density ( N bt ) near the AlNO/AlGaN interface is also identified to be reduced by the insertion of AlN layers into Al2 O3 . The PEALD induced optimization of AlNO deposition on the AlGaN/GaN heterojunction provides a pathway to the fabrication of AlGaN/GaN high electron mobility transistors (HEMTs) with low interface trap density.